Important fish and shrimp fry in the Philippines coastal waters identification, collection and handling. - Barinao, T.U; Solis, N.B; Villaver, W.R; Villaluz, A.C (SEAFDEC Aquaculture Department, 1986)
Aquaculture Extension Manual No. 10